NDVI Differencing and Post-classification to Detect Vegetation Changes in Halabja City, Iraq. - Mansor, Shattri; Mohd Shafri, Helmi Zulhaidi; Al-doski, Jwan (2013)
This study presents vegetation change detecting in Halabja city, Iraq by using Landsat-5Thematic Mapper images. This city was shelled with chemical weapons on 16 March, 1988. The Normalized Difference Vegetation Index (NDVI) image differencing and post–classification techniques were applied. The NDVI was derived first then classified to produce vegetation maps followed by quantifying the changes.The results indicated a drastic decrease in the dense, sparse and moderate vegetation by55%, 7% and 9% respectively. In contrast, the non-vegetation class increased by 5%. This means that, the field and planted areas were at risk of losing vegetation.